1996
DOI: 10.1007/bf02522617
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of eicosapentaenoic acid and docosahexaenoic acid as ethyl esters reduced plasma cholesterol and changed the fatty acid composition in rat blood and organs

Abstract: Fish oils rich in n-3 fatty acids have been shown to decrease plasma lipid levels, but the underlying mechanism has not yet been elucidated. This investigation was performed in order to further clarify the effects of purified ethyl esters of eicosapentaenoic acid (EPA-EE) and docosahexaenoic acid (DHA-EE) on lipid metabolism in rats. The animals were fed EPA-EE, DHA-EE, palmitic acid, or corn oil (1 g/kg/d) by orogastric intubation along with a chow background diet for three months. At the end the animals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
83
5
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 66 publications
10
83
5
2
Order By: Relevance
“…Obtained dependencies confirmed the theory that PUFA/MUFA in animal food has an influence on the lipid profile of animals' blood serum (i.e. an increase in HDL and decrease in LDL cholesterol levels precisely) (Froyland et al, 1996;Barowicz & Pietras, 1998). In addition, in the blood serum of the animals in Group 6, a statistically significant and higher level of HDL cholesterol was recorded compared with pigs of Group 3.…”
Section: Resultssupporting
confidence: 72%
“…Obtained dependencies confirmed the theory that PUFA/MUFA in animal food has an influence on the lipid profile of animals' blood serum (i.e. an increase in HDL and decrease in LDL cholesterol levels precisely) (Froyland et al, 1996;Barowicz & Pietras, 1998). In addition, in the blood serum of the animals in Group 6, a statistically significant and higher level of HDL cholesterol was recorded compared with pigs of Group 3.…”
Section: Resultssupporting
confidence: 72%
“…Both tretment decreased AA content and n-6/n-3 PUFA ratio in the membranes, withouht modifying the unsaturation index. 33 Froyland et al 34 clarified the effects of purified esters of EPA and DHA on lipid metabolism in rats. The animals were fed by orogastric intubation 1 g/kg/day for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…C18:3-6 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 0.07 ± 0.36 0.00 ± 0.00 C18:3-3 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 0.00 ± 0.00 C20: Some previous surveys have demonstrated a diminution in the blood pressure as consequence of n3-PUFAs [22,28], but with dosages higher than 3 g/day. In this sense, surveys with animas and humans have demonstrated that EPA and DHA are incorporated in a different way in plasma [29], platelets, cellular membranes [6] and fatty tissue [30]. According to these reports, the diminution in the SBP experienced by the SG could be due to a progressive doby accumulation of n3-PUFAs during the supplementation period.…”
Section: Discussionmentioning
confidence: 99%